Pengelolaan Embung Desa: Branding Menuju Desa Ekowisata dan Pemberdayaan Masyarakat - Suryadi Suryadi; Dyah Erlina Sulistyaningrum; Maria Yosepin Endah Listyowati; Wildan Nur Hidayatullah; Edy Prayitno; Tutik Heriana; Ria Fajar Nurhastuti (Pusat Riset dan Inovasi Nasional, 2026)
The Mbeji Teleng Reservoir in Belang Village, Bungkal District, Ponorogo, was originally built as an irrigation water catchment; however, its management had not been optimized, resulting in the underutilization of its natural, social, and economic potential. This community engagement program aims to transform the reservoir into an educational ecotourism destination while strengthening village branding and community empowerment. The methods employed include (1) enhancing community awareness of the reservoir’s multifunctional role, (2) revitalizing and organizing the reservoir area to support ecotourism infrastructure, and (3) improving community capacity and economic empowerment through training, digital promotion, and MSME facilitation. The interventions resulted in the establishment of an active tourism-awareness group (Pokdarwis), increased community understanding of water conservation, improved physical facilities and public spaces, and the development of ecotourism features such as a fishing pond and photo spots. Additionally, digital promotional media and local trading stalls were produced to support the village economy. This program introduces a novel approach by repositioning the reservoir as a multifunctional public space and integrating ecotourism with community-driven management, offering a sustainable model for rural ecotourism development.